Metaphorical Landscapes: Exploring Metaphors in Hindi, Bhojpuri and English Proverbs - Shubhra, Shubhra; Krishna, Devina (English Department, Faculty of Humanities, Andalas University, 2025)
This study, titled “Metaphorical Landscapes: Exploring Metaphors in Hindi, Bhojpuri, and English Proverbs,” investigates the intricate and culturally rich use of metaphors in the proverbs of these three languages. Proverbs, known for their brevity and depth, serve as vessels of communal wisdom, encapsulating cultural values, societal norms, and collective experiences. Metaphors within these proverbs enhance their expressive power by enabling the conveyance of abstract ideas through vivid, concrete imagery. This research seeks to uncover the underlying conceptual frameworks that shape the worldviews of Hindi, Bhojpuri, and English-speaking communities. Focusing primarily on Hindi and Bhojpuri due to their geographical and cultural proximity, this study also includes English to explore potential overlaps and borrowings in metaphorical expressions. Employing a qualitative comparative methodology, this study analyses a curated selection of proverbs to identify universal themes and distinct metaphorical constructs. Proverbs, as carriers of cultural wisdom, offer a window into the collective psyche and values of a community. Through this exploration, the present study aims to understand these metaphorical landscapes to foster empathy, cross-cultural dialogue, and a deeper appreciation of the intricate ways in which language shapes our perception of the world.